Utilization of Solid Waste as a Substrate for Production of Oil from Oleaginous Microorganisms - Laker, Fortunate; Agaba, Arnold; Akatukunda, Andrew; Gazet, Robert; Barasa, Joshua; Nanyonga, Sarah; Wendiro, Deborah; Wacoo, Alex Paul (Journal of Lipids, 2018)
The overwhelming demand of oil and fats to meet the ever increasing needs for biofuel, cosmetics production, and other industrial purposes has enhanced a number of innovations in this industry. One such innovation is the use of microorganisms as alternative sources of oil and fats. Organic solid waste that is causing a big challenge of disposal worldwide is biodegradable and can be utilized as substrate for alternative oil production.The study evaluated the potential of isolated yeast-like colonies to grow and accumulate oil by using organic solid waste as substrate. Of the 25 yeast-like colonies isolated fromthe soil samples collected fromthree different suburbs in Kampala district, Uganda, 20 were screened positive for accumulation of lipid but only 2 were oleaginous. The NHC isolate with the best oil accumulation potential of 48.8% was used in the central composite design (CCD) experiments. The CCD experimental results revealed a maximum oil yield of 61.5% from 1.25 g/L cell biomass at 10 g/L of solid waste and temperature of 25∘C. The study revealed that organic solid waste could be used as a substrate for microbial oil production.
Keywords: Solid Waste; Production; Oil; Oleaginous Microorganisms